Acid Attack on Concrete Containing Industrial Wastes - Brintha G, Shiny; N, Sakthieswaran (JOURNAL OF ADVANCES IN CHEMISTRY, 2016)
In this paper, the acid attack test is conducted on M30 grade concrete with industrial wastes. Here in this study, GGBS and metakaolin are partially replaced for cement and copper slag is replaced for sand. The simultaneous replacement of these materials is done in each mix. Totally five mixes were prepared including controlmix. GGBS and metakaolin replacement vary from 5% to10% in successive mixes. Similarly the copper slag replacement ranges from 20 to 40%. Two types of acids such as Sulphuric Acid, Hydro chloric Acid with 1%concentration are used at 28 days immersion. From the results, it is observed that the percentage loss of weight is least for the mix containing 5% GGBS, 5% Metakaolin and 20% copper slag. And also for the same mix, the compressive strength of 28 dayssulphuric acid curing is11.07% higher than the concrete with 28 days water curing. Similarly in hydro chloric acid immersion, the compressive strength of concrete is 2.24% higher than the concrete with 28 days water curing. The reason for the acid resistance of concrete is the combined effect of GGBS, Metakaolin and copper slag.